IMPLEMENTASI PENYELESAIAN SENGKETA UTANG PIUTANG DENGAN JAMINAN TANAH DAN BANGUNAN (Studi Putusan Nomor 62/Pdt.G/20222/PN.Tjk) - Tami Rusli; Aprinisa Aprinisa; Raja Kapitan Diningrat (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Darma Agung, 2023)
Accounts payable are part of socio-economic activities that usually occur in the midst of society based on the need to meet household needs or business capital. In carrying out debts, a borrower provides a guarantee such as a land certificate or object with an agreement that has been made. An agreement gives rise to the rights and obligations of the parties. The term guarantee comes from the word guarantee which means responsibility, so that guarantee can be interpreted as a dependent. The research method uses normative and empirical juridical methods. This study aims to find out about the Factors Causing the Occurrence of Debt and Credit Disputes with Guaranteed Land and Buildings and the process of Settlement of Debt and Receivable Disputes with Guaranteed Land and Buildings Based on the Study of Decision Number 62/Pdt.G/2022/PN Tjk